POTENSI MEDIA CAIR BERBAHAN ORGANIK SEBAGAI MEDIA ALTERNATIF UNTUK PERTUMBUHAN BAKTERI SEBAGAI PUPUK HAYATI (Potential of Organic Liquid Media as an Alternative Media for Bacterial Growth for Biofertilizer) - Y., A., Nion; A., A., Djaya; N., Handayani; L., Neneng (AGRIPEAT, 2016)
ABSTRACTStudies to evaluating various organic materials to propagation of bacteria as biofertilizer is still a fewand research to obtain a alternative media for growing bacteria from organic materials are cheaperhave been carried out in the laboratory Department of Agriculture, Faculty of Agriculture, Universityof Palangkaraya since September 2014 to July 2015. This study was conducted in three series ofstudies, such as at the first experiment knowing the growth of soil bacteria on the type of medianutrient broth (NB), coconut water, mung bean sprouts wastewater, tofu wastewater, rice washingwater, boiled fish bones and boiled chicken bones up to 5 days after inoculation (dai), a second seriesknowing the growth of bacteria Burkholderia nodosa G5.2rif1 up to 14 dai in NB media, boiledshrimp shells, boiled snails meat and boiled catfish belly, a third series was to determine the growth ofB. nodosa G5.2rif1 on media media NB, potato dextrose liquid, coconut water, tofu wastewater, andcoconut oil. The conclusion is medium coconut water, mung bean sprouts waswater, tofu wastewater,rice washing water, boiled fish bones, boiled chicken bones, boiled shrimp shell, boiled a snails meat,boiled catfish belly, and potato dextrose liquid is able to increase the growth of bacteria highercompared than commercial media, as a alternative media substitute cheaper than commercial nutrientbroth. Media alternatives that faster growth for soil bacteria is wastewater of mung bean sprouts andrice washing water while good media for faster promote growth of B. nodosa G5.2rif1 is boiled catfishbelly, boiled snail meat, potato dextrose liquid, coconut water and tofu wastewater.Keywords: bacteria, biofertilizer, liquid media, organic matter, potency.